Antibacterial Properties of Novel Bacterial Cellulose Nanofiber Containing Silver Nanoparticles - 杨加志 刘晓丽 黄立勇 孙东平 (Chinese journal of chemical engineering, 2013)
In this work, we describe a novel facile method to prepare long one-dimensional hybrid nanofibers by using hydrated bacterial cellulose nanofibers（BCF） as a template. Silver（Ag） nanoparticles with an average diameter of 1.5 nm were well dispersed on BCF via a simple in situ chemical-reduction between AgNO3 and NaBH4 at a relatively low temperature. A growth mechanism is proposed that Ag nanoparticles are uniformly anchored onto BCF by coordination with BC-containing hydroxyl groups. The bare BCF and as-prepared Ag/BCF hybrid nanofibers were characterized by several techniques including transmission electron microscopy, X-ray diffraction, thermogravimetric analyses, and ultraviolet-visible（UV-Vis） absorption spectra. The antibacterial properties of Ag/BCF hybrid nanofibers against Escherichia coli（E. coli, Gram-negative） and Staphylococcu saureus（S. saureus, Gram-positive） bacteria were evaluated by using modified Kirby Bauer method and colony forming count method. The results show that Ag nanoparticles are well dispersed on BCF surface via in situ chemical-reduction. The Ag/BCF hybrid nanofiber presents strong antibacterial property and thus offers its candidature for use as functional antimicrobial agents.